Pulmonary venous isolation by antral ablation with a large cryoballoon for treatment of paroxysmal and persistent atrial fibrillation: medium-term outcomes and non-randomised comparison with pulmonary venous isolation by radiofrequency ablation. Issue 17 (26th August 2010) - Kojodjojo, Pipin; O'Neill, Mark D; Lim, Phang Boon; Malcolm-Lawes, Louisa; Whinnett, Zachary I; Salukhe, Tushar V; Linton, Nicholas W; Lefroy, David; Mason, Anthony; Wright, Ian; Peters, Nicholas S; Kanagaratnam, Prapa; et al.
Abstract : Background: To prevent atrial fibrillation (AF) recurrence after catheter ablation, pulmonary venous isolation (PVI) at an antral level is more effective than segmental ostial ablation. Cryoablation around the pulmonary venous (PV) ostia for AF therapy is potentially safer compared to radiofrequency ablation (RFA). The aim of this study was to investigate the efficacy of a strategy using a large cryoablation balloon to perform antral cryoablation with 'touch-up' ostial cryoablation for PVI in patients with paroxysmal and persistent AF. Methods: Paroxysmal and persistent AF patients undergoing their first left atrial ablation were recruited. After cryoballoon therapy, each PV was assessed for isolation and if necessary, treated with focal ostial cryoablation until PVI was achieved. Follow-up with Holter monitoring was performed. Clinical outcomes of the cryoablation protocol were compared, with consecutive patients undergoing PVI by RFA. Results: 124 consecutive patients underwent cryoablation. 77% of paroxysmal and 48% of persistent AF subjects were free from AF at 12 months after a single procedure. Over the same time period, 53 consecutive paroxysmal AF subjects underwent PVI with RFA and at 12 months, 72% were free from AF at 12 months (p=NS). There were too few persistent AF subjects (n=8) undergoing solely PVI by RFA as a comparison group. Procedural and fluoroscopic times during cryoablation were significantly shorter than RFA. Conclusions: PV isolation can be achieved in less than 2 h by a simple cryoablation protocol with excellent results after a single intervention, particularly for paroxysmal AF.